Community Response On Changes Regional Head Election System (Study On Environmental Public Housing Way Kandis Bandar Lampung) - Wawan Hernawan; Mutia Ravenska (Bandar Lampung University, 2015)
This study aims to determine the public response about Regional Head Election system changes that occurred in Indonesia as well as the public wants to know about the system of local elections process viewed from the perspective of science communication. The approach used in this study is a qualitative approach, collecting data using observation, interviews, and documentation.The results showed that the public response of the society of Way Kandis, Bandar Lampung did not agree to a system of Regional Head election conducted by the Regional Representatives Council. The society prefers Regional Head election system is implemented directly, elected by the people. Thus the response shows that Indonesia is a country that adheres to the principles of democracy; the society has a control function to a policy made by the government.